2019
DOI: 10.1007/s11121-019-01029-x
|View full text |Cite
|
Sign up to set email alerts
|

Applying Natural Language Processing to Evaluate News Media Coverage of Bullying and Cyberbullying

Abstract: Bullying events have frequently been the focus of coverage by news media, including news stories about teens whose death from suicide was attributed to cyberbullying. Previous work has shown that news media coverage is influential to readers in areas such as suicide, infectious disease outbreaks, and tobacco use. News media may be an untapped resource to promote bullying prevention messages, though current news media approaches to describing bullying and cyberbullying remain unexplored. The purpose of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…This study finding is supported by previous work that compared fear-based to public health-oriented news articles using linguistic analysis (Moreno et al 2019). That study found that fear-based articles were more likely to include negative emotion words related to anxiety, anger, and death.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This study finding is supported by previous work that compared fear-based to public health-oriented news articles using linguistic analysis (Moreno et al 2019). That study found that fear-based articles were more likely to include negative emotion words related to anxiety, anger, and death.…”
Section: Discussionsupporting
confidence: 87%
“…Alongside the reader's own experience of bullying, the news media's choice of words might also be perpetuating these feelings of sadness and hopelessness. In fear-based news articles, the use of negative emotion words related to anxiety, anger, and death could contribute to the participant's emotional responses to the excerpt (Moreno et al 2019). The use of emotional words has been shown to play a significant role in the perception of news media (Hoffner et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations